A partial transmit sequence technique with error correction capability and low computation. (15th July 2013) - Liang, Hsin‐Ying; Chu, Hung‐Chi; Lin, Chuan‐Bi; Lin, Kuang‐Hao
SUMMARY Orthogonal frequency division multiplexing (OFDM) is a popular transmission technique in wireless communication. Although already widely addressed in many studies, OFDM still has flaws, one of which is the occurrence of high peak‐to‐average power ratio (PAPR) in the transmission signal. The partial transmit sequence (PTS) technique is one method adopted to reduce high PAPR in OFDM systems. However, as PTS utilizes phase factors to generate multiple candidate signals, large amounts of calculation and time are required to search the candidate signal with the minimal PAPR, which will then be adopted as the final transmission signal. This paper proposes a novel PAPR reduction method, which can be applied in OFDM systems with M‐ary phase‐shift keying modulation. It not only requires less computation but also possesses error correction capabilities. More precisely, the proposed method is to divide a block‐coded modulation code into the direct sum of a correcting subcode for encoding information bits and a scrambling subcode for generating phase factors. Our proposed method is a suboptimal technique with low computation, because it uses a genetic algorithm with a partheno‐crossover operator as the transmitted signal selection mechanism. Simulation results show our proposed method has better PAPR performance than the GA‐PTS scheme. Based on the simulation results in Figures 5 and 6, it is evident that our proposed method can be employed in any OFDM system by using M‐PSK modulation.Copyright © 2013 John Wiley & Sons, Ltd.